НАУКОВЕ ОБҐРУНТУВАННЯ ОСНОВНИХ ПІДХОДІВ ДО МОТИВАЦІЇ ФАРМАЦЕВТИЧНИХ ПРАЦІВНИКІВ - Тетерич, Н. В. (Фармацевтичний часопис, 2015)
УДК: 615.15:005.32:331.101.3 SCIENTIFIC GROUND OF BASIC GOING IS NEAR MOTIVATION OF PHARMACEUTICAL WORKERS N.V. Teterich National university of pharmacy, Kharkov Entry. Now as plain as a pikestaff is that for the sake of achievement of success in competitive activity at the pharmaceutical market very a necessity is bringing in of highly skilled pharmaceutical shots, in fact it is known that efficiency of any activity directly depends on a beautifully neat personnel. A research purpose is an analysis of social psychology factors and ground of the basic going near the increase of motivation of pharmaceutical workers. Research methods. For the decision of the put purpose testing of pharmaceutical workers was applied after the selected psychological methods which determine the factors of social orientation them labor motivation is a level of motivation to approval after the method of D. Kroun-D. Marlou, and also level of motivation to success after the method of Т. Elersa. As a result of the conducted research generalization of independent descriptions of specialists was carried out. Results and discussions. During research the selective complex questioning was conducted 30 pharmacists of pharmacy establishments of different boroughs ofKharkov after these methods. Before working 30 polling cards of tests were accepted on every method offered to specialists. A level of motivation to approval is one of major necessities of man from satisfaction of which depends it internal self-awareness and position in a group. Substantial influence has thus this type of motivation on quality of interpersonality mutual relations. Results of working of information are after the method of D. KROUNA-D. Marlou set that swingeing majority of specialists - 22 the polled (73,33%) is had middle level of motivation to approval. Only three specialists - 10% specialists have a low level of motivation to approval. Usually these workers are a conflict and independent of ideas from the side of circumferential, that can put them out of social approval. Finally, five the polled (16,67 %) is had high motivation to approval. These specialists do not have denials in relation to labor, restrain the aggressive reactions, and need enhanceable intercourse. The analysis of testing of pharmaceutical workers set after the method of T. Elersa, that for specialists with the high level of social desirability the low level of motivation absents to success; the middle level of motivation to success appeared at 3 респондентів (60%) and high level to motivation present for 2 specialists (40 %). Thus superfluously high level of motivation to success with specialists with the high level of motivation lack of to approval. A level of motivation to success of workers with the middle level of social desirability is such: low level of motivation to success in this investigated lack of in group of specialists; a middle level of motivation is to success with 15 respondents (68,18%); high level to motivation present for five specialists (22,73%); ever-higher level of motivation to success with two specialists - 9, 09%. A level of motivation to success of pharmaceutical specialists with the low level of motivation to approval is following: low level of motivation to success in this investigated group lack of of specialists also; 2 specialists has a middle level of motivation to success (66,67%); high level of motivation to success with one specialists (33,33%). Conclusions. The analysis of literary sources rotined on questions professional motivation of pharmaceutical workers, that study of going near professional motivation in pharmacy not used practically. The analysis of individual indexes of motivation of labor activity of pharmaceutical workers of social psychology direction is carried out Certainly straight proportional dependence of social desirability of specialists with the level of their motivation to success.